Compared social protection systems: the cases of colombia, brazil, and mexico (2002)
A compared analysis of the social protection systems of Colombia, Brazil, and Mexico is considered, under the assumption that those systems are one part within the set of systems of mediation and articulation between politics and economy. The evolution of the protection systems of Brazil, Mexico, and Colombia since 1930 until 1990, and then during the reform period of the 90s is examined. An analysis of the determinants of the configuration and reform of the systems is performed, proposing some hypothesis about the social protection systems evolution.